Komodifikasi Agama dalam Era Digital (Studi Etnografi Virtual Fenomena Cek Khodam di Media Sosial) - Fuadi, Muhamad Hanif Fuadi; Ramadhanita, Frista Fitriany (Jurnal komunikan, 2025)
This study examines the phenomenon of religious commodification in the digital era, focusing on the practice of checking khodam on social media. Using a virtual ethnographic approach, the study analyzes how traditional spiritual practices are transformed into digital commodities. The results of the study show that khodam checks on social media are a form of religious commodification that involves commercialization, standardization, and personalization of spiritual services. This phenomenon reflects a shift in religious practices in the digital society and raises questions about authenticity and ethics in online spirituality.